2011
DOI: 10.1177/0091270010382909
|View full text |Cite
|
Sign up to set email alerts
|

Mycophenolic Acid Pharmacokinetics During Maintenance Immunosuppression in African American and Caucasian Renal Transplant Recipients

Abstract: Renal transplant recipients exhibit variability in mycophenolic acid (MPA) and MPA glucuronide (MPAG) pharmacokinetics, which are influenced by clinical and demographic factors. Racial influence on MPA and MPAG pharmacokinetics was investigated in 53 patients: 17 African American males, 22 Caucasian males, and 14 females receiving mycophenolate mofetil (MMF) and cyclosporine. A 12-hour steady-state pharmacokinetic study was conducted. Enterohepatic circulation of MPA was characterized by a second plasma concen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
36
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 24 publications
(39 citation statements)
references
References 47 publications
2
36
1
Order By: Relevance
“…Without TDM, our cohort of African American patients would have presumably been underdosed by receiving standard dosing of 600 mg/m 2 . Although this finding has been corroborated in adult patients, this was not reported yet in pediatric heart transplant studies . Dipchand and Gajarski's findings that younger patients required higher dosing per body weight to achieve therapeutic MPA levels when compared to older patients were not assessed in our study .…”
Section: Discussionmentioning
confidence: 45%
“…Without TDM, our cohort of African American patients would have presumably been underdosed by receiving standard dosing of 600 mg/m 2 . Although this finding has been corroborated in adult patients, this was not reported yet in pediatric heart transplant studies . Dipchand and Gajarski's findings that younger patients required higher dosing per body weight to achieve therapeutic MPA levels when compared to older patients were not assessed in our study .…”
Section: Discussionmentioning
confidence: 45%
“…Whether there are differences in MPA exposure among races remains controversial; however, some data have suggested that MPA dose reductions lead to more frequent rejection in blacks than non-black patients (10,38,39). Additionally, earlier data demonstrated that higher MPA dosing benefitted black patients treated with cyclosporine when compared with non-blacks, although this finding has not been clearly elucidated in the context of tacrolimus-based regimens (40). Also of note, it has been have shown that black patients require higher doses of cyclosporine and tacrolimus to achieve comparable levels in black patients as in non-black patients, seemingly due to the fact that more black patients have CYP3A5 polymorphisms that lead to rapid metabolism of CYP450 3A isoenzyme substrates (41,42).…”
Section: Discussionmentioning
confidence: 99%
“…inspection of the MPA concentration vs. time profiles for appearance of a second peak occurring from 6 to 12 over the dosing interval ; b) an increase in MPA concentration greater than 25% compared to the previous time point during the elimination phase [16,17, 32]. …”
Section: Methodsmentioning
confidence: 99%
“…Clinical and demographic factors contribute to interpatient variability in MPA and MPAG pharmacokinetics and include renal function, race, sex, albumin, hemoglobin, hematocrit, age, calcineurin inhibitor therapy and time post-transplant [1, 15, 16]. Prior research has described race differences in MPA and MPAG pharmacokinetics with MMF or ECMPS in African American (AA) and Caucasian renal transplant recipients receiving cyclosporine with a suggested sex influence [16, 17]. These studies were unique due to inclusion of intensive pharmacokinetic sampling with statistical models including pertinent clinical covariates to assess variability.…”
Section: Introductionmentioning
confidence: 99%